Hip surgery : An odyssey - Sarmiento, Augusto (Jaypee Brothers Medical Publishers, 2012)
Hip Surgery: An Odyssey is a step by step journey through important technological developments in hip surgery. Based on the author's personal experiences, the book examines past and present procedures, their successes and complications. Enhanced by more than 600 well-illustrated images, this text discusses different types of hip surgery - reconstructive surgery, including total hip arthroplasty; specific pathological conditions, the fractured hip and annexures.